Variasi Fungsi Predikat dalam Kalimat Tunggal Bahasa Indonesia: Analisis pada Teks Akademik Mahasiswa - Ubaidillah, Umair; Al-farizy, Faiz; Kadiatmaja, Agung Pranoto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the variation of predicate functions in Indonesian simple sentences found in students’ academic texts. The study is based on the importance of predicate functions in constructing clear, logical, and systematic academic sentences. However, students’ academic writing still tends to use limited and less varied predicate structures, resulting in monotonous sentence patterns. This research employed a qualitative approach using a descriptive analysis method. The data consisted of simple sentences collected from academic texts, scientific journals, and relevant books. The analysis focused on identifying and classifying predicate functions, including verbal, nominal, adjectival, and prepositional predicates. The findings reveal that verbal predicates are the most dominant form used by students because they effectively convey actions and processes in academic writing. In addition, nominal and adjectival predicates were found to function in expressing identity and conditions, while prepositional predicates indicate structural variation in sentence construction. These findings demonstrate that predicate variation is not only related to grammatical aspects but also reflects students’ academic thinking patterns. Therefore, understanding predicate functions is essential to improve students’ academic writing skills and sentence effectiveness.